2021
DOI: 10.3389/fimmu.2021.792609
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of the Bone Marrow Microenvironment Reveals Distinct Immunotypes in Smoldering Multiple Myeloma Associated to Progression to Symptomatic Disease

Abstract: BackgroundWe previously reported algorithms based on clinical parameters and plasma cell characteristics to identify patients with smoldering multiple myeloma (SMM) with higher risk of progressing who could benefit from early treatment. In this work, we analyzed differences in the immune bone marrow (BM) microenvironment in SMM to better understand the role of immune surveillance in disease progression and to identify immune biomarkers associated to higher risk of progression.MethodsGene expression analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…MM is the second most common hematological malignancy, generating monoclonal plasma cells associated with immunoglobulin production. Previous studies have shown that the expression of EZH2 plays an essential role in the developmental differentiation of B cells [31]. In MM, EZH2 overexpression is involved in biological processes including proliferation, apoptosis and side-population maintenance of tumor cells, and is also associated with cellular drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…MM is the second most common hematological malignancy, generating monoclonal plasma cells associated with immunoglobulin production. Previous studies have shown that the expression of EZH2 plays an essential role in the developmental differentiation of B cells [31]. In MM, EZH2 overexpression is involved in biological processes including proliferation, apoptosis and side-population maintenance of tumor cells, and is also associated with cellular drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In the third stage, the immune microenvironment is characterized by the widespread suppression and inactivation of cytotoxic cells and disease progression (Fernandez et al, 2022). Another study has reported similar alterations (Isola et al, 2021). Patients with HR SMM is not only characterized by the enrichment of gene sets associated with cytotoxic responses, including Tbet, perforin, granzyme b (GZMB), and granulysin, but also by the overexpression of suppressor molecules such as TIGIT,and IDO1 (17).…”
Section: Nk Cells Change Parallel To Myeloma Progressionmentioning
confidence: 98%